The Influence of Apparatus Competence, Individual Morality, Internal Control System, Whistleblowing System on Village Fund Fraud Prevention - Dominika Apriliani Lahu; Gayatri (International Journal of Economics Accounting and Management, 2024)
The objective of this study is to explore the impact of apparatus competency, individual morality, internal control systems, and whistleblowing systems in preventing fraud related to village funds. The research population includes all village officials, members of the Village Consultative Body (BPD), village fund supervisors, and community leaders in Ruteng District, Manggarai Regency. The sample consists of Village Heads, Village Secretaries, Heads of Finance, Heads of BPD, village fund supervisors, and community leaders from each village in Ruteng District. Path analysis is the technique used for data analysis. The study finds that apparatus competency, individual morality, internal control systems, and whistleblowing systems positively influence the prevention of fraud in village fund management. In summary, competent officials perform their duties in managing village funds responsibly, high-morality officials are less likely to engage in misconduct, and effective supervision ensures village management activities are directed and monitored to prevent fraud.